Cephalometric Evaluation of Class III Malocclusion Cases with Different Vertical Facial Development - Eröz Dilaver, Barçın; Beşer, Büşra; Çelebi Erdivanlı, Özlem; Dursun, Engin (ENT Updates, 2020)
Objective: The purpose of the present study was to investigate the relationship between vertical facial development and angular and linear measurements of the face. Methods: Pretreatment cephalometric radiographs of subjects with class III malocclusion were divided into three groups according to vertical facial development as low, normal and high angle. Nine angular, three dimensional and one ratio measurements were performed with the analysis program (AudaxCeph ver. 5.2.0.3610, Audax Slovenia) on the cephalometric radiographs and compared between the vertical growth groups. Results: There was a significant negative correlation between the Sella-Nasion/Gonion-Menton (SN-GoMe) and Saddle-Nasion-A (SNA), Saddle-Nasion-B (SNB), Incisal Mandibular Plane Angle (IMPA) and Jarabak ratio measurements, whereas a significant positive correlation was found between the SN-GoMe and the Gonial and Saddle measurements. Conclusion: According to the results of the present study, we determined that anterior and posterior development of the face decreases with the increase in the vertical direction of the face. Also, an increase in vertical direction angles including Gonial and Saddle angles significantly correlated with the increase in SN-GoMe angle. Since vertical growth problems can cause complicated and long orthodontic treatment, factors that may affect vertical growth should be addressed, such as mouth breathing.